Efektifitas Motion Graphic sebagai Media Pendidikan Gizi pada Karyawan di Masa Pandemi - Ratna Dwi Ismianti; Laras Sitoayu; Rachmanida Nuzrina; Yulia Wahyuni; Dudung Angkasa (Universitas Islam Negeri Walisongo Semarang, 2022)
The purpose of this study is to determine the effect of nutritional education through motion graphic media on knowledge and attitude of the four pillar of balanced nutrition in employees. The research is a quasy experimental study with two groups pretest-postest design. Sampling used was a purposive sampling. The target of this study is employees of Esa Unggul University who were divided into two groups, the intervention group that was given motion graphic and the control group which was not given the media, each group include 31 people. The results showed that there was an increase in knowledge in both the intervention group and the control group. Data analysis used was Mann-Whitney test. There was no difference in knowledge before intervention and there was a difference in knowledge after an intervention. As for the attitude, there was no difference in the two groups before, but there was a change in attitude in the intervention group. As the result, the study concluded that there is an effect of nutritional education with motion graphic media on the knowledge and attitude of the four pillars of balanced nutrition for Esa Unggul University’s employees. Tujuan penelitian ini adalah untuk mengetahui pengaruh pendidikan gizi melalui media motion graphic terhadap pengetahuan dan sikap empat pilar gizi seimbang pada karyawan. Jenis penelitian ini eksperimental semu dengan two group pretest-postest design. Pengambilan sampel menggunakan teknik purposive sampling. Sampel merupakan karyawan Universitas Esa Unggul yang dibagi menjadi dua kelompok yaitu kelompok intervensi diberikan media motion graphic dan kelompok kontrol hanya diberikan ceramah. Masing-masing kelompok berjumlah 31 orang. Uji beda menggunakan uji Mann Whitney. Hasil penelitian menunjukkan ada peningkatan pengetahuan baik pada kelompok intervensi maupun kelompok kontrol. Tidak ada perbedaan pengetahuan sebelum intervensi antar kedua kelompok (p=0,189) dan ada perbedaan pengetahuan setelah intervensi antar kedua kelompok (p=0,001). Adapun untuk sikap, tidak ada perbedaan antar kedua kelompok sebelum (p=0,365) dan sesudah intervensi (p=0,435). Terdapat peningkatan sikap yang signifikan pada kelompok intervensi. Terdapat pengaruh pendidikan gizi dengan media motion graphic terhadap pengetahuan dan sikap empat pilar gizi seimbang pada karyawan.